Analisis Kemampuan Pemecahan Masalah Matematis Siswa SMA Kelas XI SMAN 1 Bangkinang Kota Ditinjau dari Gaya Belajar - Syahril, Ravina Faradilla; Maimunah, Maimunah; Roza, Yenita (Edumatica : Jurnal Pendidikan Matematika, 2021)
This study aims to describe the mathematical problem solving ability of students and the relationship between KPMM and student learning styles, especially on the material of the Three Variable Linear Equation System. This research uses mixed methods, combining quantitative and qualitative research. The subjects in this study were students of class XI of SMAN 1 Bangkinang Kota for the academic year 2021-2022 as many as 20 people. The instrument used is a mathematical problem solving ability test which consists of 5 items with 4 KPMM indicators according to Polya and a student learning style questionnaire. The results of this study indicate that the problem solving ability of students on the indicator of understanding the problem is at a very low criterion with a percentage of 40% indicator, the indicator of planning problem solving is at a very low criterion with a percentage of 36%, the indicator of completing a problem solving plan is at a very low criterion with a percentage 36% and indicators interpret the results obtained are in very low criteria with a percentage of 22%. Mathematical problem solving ability has nothing to do with the learning style possessed by students. Every student with any learning style has the same tendency to solve problems. Based on the results of the study, it shows that students are not accustomed to working on non-routine questions such as problem solving questions, so students need to get used to working on non-routine questions, especially those that can train students' problem solving skills.